(untitled) (LACCEI, 2024)
Information technologies are the perfect medium for the development of multidisciplinary proposals that contribute to the development of digital media for the benefit of society on climate monitoring and monitoring. The objective of this research is to develop a prototype of a low-cost mini-weather station with cloud service through Arduino, PHP and MySQL. Methodological design includes the identification of technological resources, design, coding, testing and implementation. In this first approach, the mini-meteorological station allows obtaining data on environmental temperature, relative humidity and atmospheric pressure. The tests were carried out during the years 2017,2018 and 2019 in order to assess the operability of the prototype in different seasons of the year. The data quality performance represents an accuracy of 93.76% for the ambient temperature variable, 99% for atmospheric pressure and 50% for relative humidity. It is recommended that in future research an FC-37 rain sensor and a JL-FS2 anemometer be integrated into the prototype to measure wind speed.